Exposure to metals during pregnancy and neuropsychological development at the age of 4 years - Forns, Joan; Fort, Marta; Casas, Maribel; Cáceres, Alejandro; Guxens, Mònica; Gascon, Mireia; Garcia-Esteban, Raquel; Julvez, Jordi; Grimalt, Joan O.; Sunyer, Jordi (Neurotoxicology (Park Forest South), 2014)
There is insufficient epidemiological evidence for deciding whether prenatal exposure to the current low-levels of metals in developed countries may affect neuropsychological function in early childhood. Our goal was to evaluate potential neurotoxic effects of prenatal exposure to seven metals (cobalt, copper, arsenic, cadmium, antimony, thallium and lead), during the 1st and 3rd trimester of pregnancy, on child neuropsychological development at 4 years of age. This study was based on a population-based birth cohort established in Sabadell (Catalonia, Spain) as part of the INMA [Environment and Childhood] Project. Metals were measured in 485 urine samples collected from mothers during the 1st and 3rd trimester of pregnancy. We assessed the neuropsychological development of 553 4-year-olds with the McCarthy Scales of Childrens' Abilitites (MSCA), together with their ADHD symptomatology, using the ADHD-DSM-IV criteria. A total of 385 children were included in the present study. We found no statistically significant associations between metals and general cognitive scale or executive function of the MSCA. We found negative coefficients for the exposure to cadmium 1st trimester, cadmium 3rd trimester and lead 3rd trimester on the general cognitive score of MSCA, although these results were not significant. We did not find any association between prenatal exposure to metals and ADHD symptomatology at the age of 4 years. Our results do not suggest that prenatal exposure to current low-levels of metals impairs children's cognitive development during preschool years.